Kedudukan Hak Asuh Anak Pasca Terjadinya Perceraian dari Istri yang Murtad menurut Hukum Islam - Lubis, Syaddan Dintara (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Provisions for Child Custody Based on the Compilation of Islamic Law are Islamic, mature, of sound mind, trustworthy, unmarried, able to educate children. There are no hadanah for non-Muslims and require women who carry out hadanah (caring for children) to be Muslim, and there are no rights and authority for those (women) who are apostates (non-Muslims) to care for children. This research aims to find out more about the provisions on child custody based on the compilation of Islamic law and child custody due to divorce due to apostasy from a wife according to the compilation of Islamic law using normative methods that collect and analyze data so as to obtain a clear picture of the problem being discussed. written work, with the aim of depicting or illustrating the occurrence of a problem systematically, factually and accurately as well as in order to obtain the truth in the process of perfecting this writing. The results of the research show how the provisions for child custody are based on a compilation of Islamic law and child custody rights from divorce due to apostasy according to the compilation of Islamic law. Key words: child custody, divorce, apostate wife.